COMBINED DISORDER: CURRENT STATUS OF METABOLIC DYSFUNCTION-ASSOCIATED FATTY LIVER DISEASE IN PATIENTS WITH HYPOTHYROIDISM AND PROSPECTS FOR PATIENT PATHWAY IMPLEMENTATION - Psarova, Valentyna; Cherkashyna, Anastasiia (Eastern Ukrainian Medical Journal, 2025)
Introduction. Metabolic dysfunction-associated steatotic liver disease is recognized as a leading manifestation of metabolic dysfunction in the general population. Along with this, hypothyroidism is becoming increasingly important as a metabolic trigger that contributes to the formation of hepatic steatosis, insulin resistance, lipid profile disorders, and progression to steatohepatitis and fibrosis. Despite abundant evidence of a pathogenetic link between hypothyroidism and metabolic dysfunction-associated steatotic liver disease, current clinical practice remains fragmentary regarding the early detection of the associated pathology. This necessitates the development of integrated approaches to screening, diagnosis, and management of patients with this comorbidity, including the formation of a patient pathway at an interdisciplinary level. Objective. The objective of the study was to summarize current data on the pathogenetic links between hypothyroidism and metabolic dysfunction-associated steatotic liver disease, analyze current approaches to the diagnosis of this combined disorder, and determine the prospects for implementing an individualized patient pathway taking into account the characteristics of both diseases. Methods. A comprehensive literature review was conducted using sources from PubMed, Scopus, and Web of Science databases over the past 5–10 years. Publications related to the pathophysiological relationship between hypothyroidism and hepatic steatosis, as well as the epidemiology of the associated disorder, diagnostic approaches, and recommendations for the management of such patients, were reviewed. Special attention was paid to the analysis of clinical guidelines and modern patient pathway algorithms for patients with metabolic disorders. Results and Discussion. The analysis demonstrated a close relationship between hypothyroidism and the risk of developing metabolic dysfunction-associated steatotic liver disease, with an emphasis on the role of thyroid hormones in the regulation of lipid metabolism, glucose metabolism, inflammation, and fibrogenesis in the liver. Even subclinical hypothyroidism was found to be associated with a significantly increased risk of steatosis, especially in patients with obesity, type 2 diabetes, or dyslipidemia. At the same time, modern patient management algorithms rarely include mandatory assessment of thyroid status, which complicates the identification and control of secondary factors of disease progression. The prospects are discussed for implementing a patient pathway that includes early thyroid function testing, interdisciplinary coordination among a gastroenterologist, endocrinologist, and family physician, as well as the potential role of therapy in certain categories of patients with concomitant metabolic dysfunction-associated steatotic liver disease. Conclusions. Hypothyroidism is an important factor in the progression of metabolic dysfunction-associated steatotic liver disease, affecting lipid metabolism, inflammation, and fibrosis. The establishment of a pathogenetic link between these diseases justifies the need for an integrated approach to patient management with mandatory thyroid screening, which, in combination with non-invasive stratification of liver fibrosis, allows for the timely detection of progressive forms of steatosis. The implementation of a clinical pathway will allow for optimizing treatment management with enhanced interdisciplinary interaction, and will also improve the long-term prognosis for patients with this comorbidity.